2019
DOI: 10.1002/nop2.389
|View full text |Cite
|
Sign up to set email alerts
|

An explorative study of workplace violence against nurses who care for older people

Abstract: AimTo explore the prevalence of workplace violence among nurses who care for older people and its association with working stress, job satisfaction and quality of care in Jordan.DesignA cross‐sectional design was used.MethodsA cluster random sampling was used to select three public hospitals, three private hospitals and 17 healthcare centres in Amman, Jordan. The researcher used a convenience sampling method to select 485 nurses. Data were collected between 2015–2016.ResultsAlmost 60% of the participants have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
(44 reference statements)
1
11
0
Order By: Relevance
“…Yenealem et al [23] detected with the Workplace violence tool an incidence of aggression in 58.2% of nurses in northwest Ethiopia. A similar result measured by Workplace violence tool reported El-Hneiti et al [7] in Jordan. Dimunová et al [24] identified with the VAPS tool [15] an incidence of aggression in 97.2% of Slovak nurses in hospital.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Yenealem et al [23] detected with the Workplace violence tool an incidence of aggression in 58.2% of nurses in northwest Ethiopia. A similar result measured by Workplace violence tool reported El-Hneiti et al [7] in Jordan. Dimunová et al [24] identified with the VAPS tool [15] an incidence of aggression in 97.2% of Slovak nurses in hospital.…”
Section: Discussionsupporting
confidence: 86%
“…Aggression of hospitalized patients towards nurses is a worldwide, long-discussed and dealt with problem [1][2][3][4][5][6][7]. Nurses are most exposed to different forms of patient aggression, with verbal attacks being most prevalent [8].…”
Section: Introductionmentioning
confidence: 99%
“…Violence can come from various sources within healthcare organisations. Studies (AbuAlRub and Al-Asmar, 2014; Albashtawy, 2013; Ayrancı, 2005; Babiarczyk et al, 2020; Bawakid et al, 2017; Boafo and Hancock, 2017; Boafo et al, 2016; Çelik et al, 2007; Cheung and Yip, 2017; Cheung et al, 2018; El-Hneiti et al, 2020; Esmaeilpour et al, 2011; Gates et al, 2006; Havaei et al, 2020; Khoshknab et al, 2015; Kowalenko et al, 2013; Lafta and Falah, 2019; Özcan and Bilgin, 2011; Mento et al, 2020; Pınar and Uçmak, 2011) showed that the most common perpetrators were patients and/or patients’ relatives.…”
Section: Conceptual Developmentmentioning
confidence: 99%
“…Hahn et al (2010) found that violence by patients and visitors is stressful for nurses. In addition, studies (Baydın and Erenler, 2014; Budd et al, 1996; Cheung et al, 2018; El-Hneiti et al, 2020; Heponiemi et al, 2014; Hesketh et al, 2003; Shahzad and Malik, 2014; Zhao et al, 2018) showed that workplace violence affects and reduces job satisfaction of healthcare employees, especially nurses. However, some studies (Boafo et al, 2016; Shahzad and Malik, 2014) have found that violence is not reported by those who have suffered it.…”
Section: Conceptual Developmentmentioning
confidence: 99%
“…The World Health Organization (WHO) defines workplace violence (WPV) as incidents where employees are subjected to harassment, threats, or attacks while engaged in job-related activities. Emergency nurses are most at risk, with violent encounters reported in 98% of Iran, 86.1% of Egypt, 74.4% of Turkey, 59%-70% in Sweden and England, 62% in Taiwan, and, 67% in Italy, 94% in Jordan, 90.9% in Saudi Arabia [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%